Psycho-Social Behavioural Problems In Urban Primary School Children - Gupta, S C; Dabral, S B; Nandan, Deoki; Mehrotra, A K; Shrotriya, V P; Maheshwari, B B (Indian Journal of Community Health, 1997)
Research Problem: What is the magnitude and correlates of psychosocial behavioural problems in primary school children of an urban area. Objectives: i) To know the prevalence of psychosocial behavioural problems in primary school children of Agra Corporation. ii) To see the impact of various biosocial factors on the prevalence of above problems. Design: Cross sectional study by questionnaire method and observation. Setting: Primary schools run by Agra Corporation. Participants: All the children studying in 7 primary schools selected from 108 schools run by Agra Corporation. Sample Size: 520 primary school children. Study Variables: Age, sex, socio-economic class and family size. Statistical Analysis: By percentage, Z - test and Chi-square test. Result: A majority of the study children (63.7%) were having some psychosocial behavioural problem or the other, the most common problem being educational difficulties (59.8%), The average number of problems per child was 2.9. The prevalence was highest in children from middle-sized families of low socioeconomic class and in age group above 13 years.